PERLINDUNGAN HUKUM TERHADAP KONSUMEN (PENERIMA PINJAMAN) FINANCIAL TECHNOLOGY YANG BERBASIS PEER TO PEER LENDING DI INDONESIA - Dita Tania Pratiwi; Sri Bakti Yunari (Jurnal Hukum Adigama, 2020)
Financial technology based peer to peer services and loan lending is based on information technology, borrowed money but in practice the financial technology based peer to peer lending is much violations. As for the problems raised is how legal protection to consumer credit recipients of borrower unlawful act carried out by lenders financial technology based peer to peer, lending and how legal remedy that can be done by consumers received loans for unlawful act carried out by lenders financial technology based peer to peer lending in Indonesia. The methodology used normative. Research is the type of secondary law obtained analyzed in the prescriptive. The analysis, obtained implies that legal protection to consumer credit recipients fintech is to carry out the principles that set in POJK 77 /POJK.01/2016, perform consumer business and the industry and both during the online transaction. While judicial remedies that can be done by the consumer credit recipients may submit complaints to OJK, make a report to BPSK, consumers and filed a lawsuit in civil and criminal to court. As a suggestion needs to be strict regulations in terms of monitoring activities. fintech in Indonesia.